Development of the mesospheric Na layer at 69 N during the Geminids meteor shower 2010 - Dunker, T.; Hoppe, U.-P.; Stober, G.; Rapp, M. (München : European Geopyhsical Union, 2013)
The ECOMA sounding rocket campaign in 2010 was performed to investigate the charge state and number density of meteoric smoke particles during the Geminids meteor shower in December 2010. The ALOMAR Na lidar contributed to the campaign with measurements of sodium number density, temperature and line-of-sight wind between 80 and 110 km altitude over Andøya in northern Norway. This paper investigates a possible connection between the Geminids meteor shower and the mesospheric sodium layer. We compare with data from a meteor radar and from a rocket-borne in situ particle instrument on three days. Our main result is that the sodium column density is smaller during the Geminids meteor shower than the winter average at the same latitude. Moreover, during two of the three years considered, the sodium column density decreased steadily during these three weeks of the year. Both the observed decrease of Na column density by 30% and of meteoric smoke particle column density correlate well with a corresponding decrease of sporadic meteor echoes. We found no correlation between Geminids meteor flux rates and sodium column density, nor between sporadic meteors and Na column density (R = 0.25). In general, we found the Na column density to be at very low values for winter, between 1.8 and 2.6 × 1013 m−2. We detected two meteor trails containing sodium, on 13 December 2010 at 87.1 km and on 19 December 2010 at 84 km. From these meteor trails, we estimate a global meteoric Na flux of 121 kg d−1 and a global total meteoric influx of 20.2 t d−1.